The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1590/s0103-84782014000400001
|View full text |Cite
|
Sign up to set email alerts
|

Reaction of common bean progenies to white mold derived from recurrent selection

Abstract: This study was realized with the objective of verifying the resistance to white mold of common bean progenies derived from recurrent selection for resistance to angular leaf spot. The plant material used was obtained from a program of recurrent selection

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 12 publications
(16 reference statements)
1
5
0
Order By: Relevance
“…Recent studies concerning white mold resistance have been conducted in Brazil to identify sources of resistance (Carvalho et al, 2013;Souza et al, 2014;Lehner et al, 2015b) or understand the genetic control of resistance (Antonio et al, 2008;Carneiro et al, 2011). In a previous study (Lehner et al, 2015b), the physiological resistance of 20 putative sources of white mold resistance from the Bean White Mold Nursery (University of Nebraska, USA) was assessed.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies concerning white mold resistance have been conducted in Brazil to identify sources of resistance (Carvalho et al, 2013;Souza et al, 2014;Lehner et al, 2015b) or understand the genetic control of resistance (Antonio et al, 2008;Carneiro et al, 2011). In a previous study (Lehner et al, 2015b), the physiological resistance of 20 putative sources of white mold resistance from the Bean White Mold Nursery (University of Nebraska, USA) was assessed.…”
Section: Introductionmentioning
confidence: 99%
“…Both the genotypes most resistant to oxalic acid (POTÊNCIA, 2010L011, P98Y30 and P98Y12) and those with higher means, that is, most sensitive to oxalic acid (P98Y51, M7639RR, M7908RR and 2010L021), expressed reactions consistent with resistance evaluated in the field. As such, in addition to the advantage of not using the etiological agent and therefore eliminating pathogen aggressiveness variability (Kull et al, 2004), this method is also not associated with the climactic effects that interfere in disease incidence and progression (Souza et al, 2014). Thus, these results confirm the potential for oxalic acid use in plant breeding programs, initially as a mass selection method to identify white mold-resistance genotypes.…”
Section: Discussionmentioning
confidence: 53%
“…In other studies, significant differences were also reported between populations improved in selection cycles, compared to the parents and progenies for the traits: hypocotyl diameter, plant architecture, grain yield and white mold susceptibility in common bean. (Souza et al 2014;Anjos et al 2018). Once the genetic divergence between treatments is known, genetic components can be estimated.…”
Section: Resultsmentioning
confidence: 99%
“…For the above-ground plant parts of common bean, numerous recurrent selection studies have already addressed variables such as crop cycle, growth habit, grain yield, grain appearance, disease resistance and others (Ramalho et al 2005;Silva et al 2010;Silva et al 2013;Souza et al 2014;Alves et al 2015;Leite et al 2016;Pereira et al 2016;Anjos et al 2018). The scarcity of studies focused on the root system might be related to the difficulty of phenotyping this trait in a large number of progenies.…”
Section: Introductionmentioning
confidence: 99%